A new opportunity for biomass-derived carbon in highly stable Li-O2 battery: A review - Guanjun Liu; Shaojie Qin; Xiping Zhang; Dan You; Yanjia Zhang; Xiaoyuan Zeng; Yiyong Zhang; Ziyi Zhu; Yingjie Zhang; Xue Li (Nano Research Energy)
Lithium-oxygen (Li-O2) battery is notable for the high theoretical energy density, and its widespread adoption has the potential to fundamentally transform the energy consumption landscape. However, the development of Li-O2 batteries has been hindered by issues such as slow reaction kinetics, high overpotential, and unstable cycle life. Rational design of cathode materials has emerged as an effective strategy for addressing these challenges. Biomass, a renewable resource, holds significant importance in the fabrication of derived carbon cathode with exceptional performance; this efficacy is largely due to its intrinsic pore structure and the presence of heteroatoms, representing a significant advancement in the field. This review outlines optimization strategies for biomass-derived carbon cathode based on the reaction mechanism of Li-O2 batteries. It introduces cross-scale characterization methods to analyze the properties of the carbon materials and explores the theoretical underpinnings of functional atom doping as a means to enhance electrochemical performance. Recent advancements in utilizing biomass-derived carbon as a porous cathode for Li-O2 batteries are assessed, highlighting the relationship between microstructural development and performance variations. Furthermore, a succinct overview of the challenges faced by biomass-derived carbon-based Li-O2 batteries is provided, along with proposed perspectives on the direction of development. This work seeks to improve the stability and catalytic efficiency of biomass-derived carbon cathode, ultimately aiming to facilitate the broader commercial application of Li-O2 battery technology.